PENERAPAN TEKNOLOGI INFORMASI DAN PENGEMBANGAN MANAJEMEN BUMDES “BANGUN YUWANA” DESA SUMBERJO KECAMATAN REMBANG, KABUPATEN REMBANG - Ahmad Aviv Mahmudi (Sekolah Vokasi Universitas Diponegoro, 2020)
Community services activities at the village’s business institution (BUMDes) Bangun Yuwana Sumberjo Village-Rembang aims to ipmrove the competence of human resources for managers of BUMDes. This activity is a part of community program implemented by STIE YPPI Rembang. BUMDes Sumberjo was officially launched in early October 2019 with 3 (three) types of bussinesses are minimarkets, photocopy services and tent/chair/ equipment rental services. In its development of BUMDes Sumberjo still experiences many obstacles including: (1) business management problems (2) operational management (3) human resources management. The results of this community service activities that have been carried out are : (1) Business motivation training, (2) Application of information technology for financial reporting and online marketing (3) Human resources and financial management training, (4) Assistance